Assessment of the innervation pattern of oral squamous cell carcinoma using neural protein gene product (9.5)–An immunocytochemical study - Habash, Fahed Samir (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: This study was carried out to assess the innervation patterns in oral cancer using the general neuronal marker protein gene product 9.5 (PGP 9.5) and to find an explanation for why oral cancer tends to be painless in the early stages. MATERIALS AND METHODS: Tumor tissue from 30 unselected patients with oral squamous cell carcinoma was evaluated for this study. PGP 9.5 was used to localize nerve fibers in oral squamous cell carcinoma. An indirect immunofluorescence technique using biotin/FITC streptavidin detection system was used on paraffin wax sections of tumor tissue fixed in neutral buffered formalin. RESULTS: There was no PGP9.5 immunoreactivity in the normal tissue adjacent to the tumor in 18 cases out of 30 (60%). In 12/30 of oral squamous cell carcinoma, preexisting nerve fibers were detected in tissue stroma adjacent to the cancer tissue. Labeled nerve fibers between tumor cells were detected only in 2 out of the 30 cases. CONCLUSION: There are no apparent patterns of innervations in the cancer tissues themselves, but there are innervations patterns in the surrounding tissue, which presumably represents preexisting nerves. These results may partly explain why oral cancer tends to be painless in the early stages.